Structure and floristic composition of a gallery forest in an altitudinal gradient in the northwest of México - Holguín-Estrada, Víctor Alfonso; Alanís-Rodríguez, Eduardo; Aguirre-Calderón, Oscar; Yerena-Yamallel, José Israel; Pequeño-Ledezma, Miguel Ángel (Instituto de Ecología, A.C., 2021)
The gallery forest is a very lush ecosystem that develops on the margins of water bodies (streams, rivers, lakes, canals, etc.) and forms a narrow strip of vegetation. This study describes the composition and partial structure of tree communities along an altitude gradient in the Las Tinajas stream, northwest of México, where three altitude ranges were considered: One (2135 m - 2366 m a.s.l.), Two (2005 m - 2093 m a.s.l.) and Three (1830 m - 1934 m a.s.l.); The specific composition, abundance, dominance, frequency, and importance value index (IVI) of the species by altitude range is analyzed. The species with the highest IVI by altitude range were: 1): Pinus durangensis (20.4%), Quercus sideroxyla (18.6%) and P. ayacahuite (14.4%). 2) Abies durangensis (25.7%), P. ayacahuite (11.5%), and Ilex tolucana (9.9%). 3): Q. crassifolia (29.1%), Cupressus lusitanica (26.4%) and Alnus oblongifolia (20.7%). Statistical analysis (ANOVA) of the abundance, dominance and richness of species shows that there are significant differences (p < 0.05) between the altitude ranges, though not significant difference was made for the Shannon index. Comparison of floristic composition based on the Bray-Curtis model achieved a similarity of less than 50% for the areas evaluated. This study will serve as a baseline of the changes that may occur in this forest in the future, the structure of the different altitude ranges was different and in each of them there are representative species.